2019
DOI: 10.1016/j.cjco.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Heart Failure After Upgrade to Cardiac Resynchronization Therapy

Abstract: Background: Cardiac resynchronization therapy (CRT) is effective in treating advanced heart failure (HF), but data describing benefits and long-term outcomes for upgrades from a preexisting device are limited. This study sought to compare long-term outcomes in de novo CRT implants with those eligible for CRT with a prior device. Methods: This is a retrospective cohort study using data from a provincial registry (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…5 Similarly, the cohort of Beca B et al, found a long-term mortality rate 2.86-fold increased. 11 On the other hand, this data differs from previously mentioned meta-analysis, and the European CRT survey, that demonstrated that CRT upgrade is associated with similar risk for all-cause mortality compared to De novo resynchronization therapy. 9 Some factors may justify these findings, firstly, it has been suggested that CRT upgrade procedures are associated with increased peri-procedural complications.…”
Section: Resultscontrasting
confidence: 87%
“…5 Similarly, the cohort of Beca B et al, found a long-term mortality rate 2.86-fold increased. 11 On the other hand, this data differs from previously mentioned meta-analysis, and the European CRT survey, that demonstrated that CRT upgrade is associated with similar risk for all-cause mortality compared to De novo resynchronization therapy. 9 Some factors may justify these findings, firstly, it has been suggested that CRT upgrade procedures are associated with increased peri-procedural complications.…”
Section: Resultscontrasting
confidence: 87%
“…On the other hand, this data differs from previously mentioned meta-analysis, and the European CRT survey, that demonstrated that CRT upgrade is associated with similar risk for all-cause mortality compared to de novoresynchronization therapy. 5,[11][12][13] Some factors may justify these findings, firstly, it has been suggested that CRT upgrade procedures are associated with increased peri-procedural complications. In fact, all in-hospital deaths occurred in the upgraded-CRT group, and directly related to the procedure.…”
Section: Discussionmentioning
confidence: 99%